Enhanced Stability and Thickness‐Independent Oxygen Evolution Electrocatalysis of Heterostructured Anodes with Buried Epitaxial Bilayers. Issue 28 (21st June 2019) - Baniecki, John D.; Yamaguchi, Hideshi; Harnagea, Catalin; Ricinschi, Dan; Gu, Zongquan; Spanier, Jonathan E.; Yamazaki, Takashi; Aso, Hiroyuki
Abstract: Achieving high oxygen evolution reaction (OER) activity while maintaining performance stability is a key challenge for designing perovskite structure oxide OER catalysts, which are often unstable in alkaline environments transforming into an amorphous phase. While the chemical and structural transformation occurring during electrolysis at the electrolyte–catalyst interface is now regarded as a crucial factor influencing OER activity, here, using La0.7 Sr0.3 CoO3− δ (LSCO) as an active OER catalyst, the critical influence of buried layers on the oxidation current stability in nanoscopically thin, chemically and structurally evolving, catalyst layers is revealed. The use of epitaxial thin films is demonstrated to engineer both depletion layer widths and chemical stability of the catalyst support structure resulting in heterostructured anodes that maintain facile transport kinetics across the electrolyte–anode interface for atomically thin (2–3 unit cells) LSCO catalyst layers and greatly enhanced oxidation current stability as the perovskite structure OER catalysts chemically and structurally transform. This work opens up an approach to design robust and active heterostructured anodes with dynamically evolving ultrathin OER electrocatalyst layers for future green fuel technologies such as conformal coatings of high‐density 3D anode topologies for water splitting. Abstract : Nanoscopically thin buried epitaxial (Sr, La)TiO3 ‐(Ba, La)SnO3 bilayers are used to achieve thickness‐independent and stable oxidation currents during the structural and chemical transformation of La0.7 Sr0.3 CoO3− δ catalysts. This work opens up an approach to design robust and active heterostructured anodes with dynamically evolving catalyst layers for future green fuel technologies such as catalyst coatings for 3D anodes for water splitting.